Community readiness to host a world-class tourism destination: Insights from lake Toba - Setiawati, Rahmi; Suhud, Usep; Allan, Mamoon; Hoo, Wong Chee (Edelweiss Applied Science and Technology, 2024)
The research focuses on the potential of the Lake Toba area for internationally recognized tourism and explores whether its local people are prepared to welcome foreign travellers. It also discusses whether traditional customs and behaviour of people around Lake Toba have limited tourism. A web survey was conducted with the aim of gathering information from visitors and locals in Lake Toba and North Sumatra to verify if they knew that the lake has been identified as a Super Priority Destination. The results were analysed based on a six-step content analysis. It is from these results that there will be the potentiality of Lake Toba to be a top-class tourist destination for all, something that should really get and inspire everybody: natural beauty, a variety of fauna and flora, nature preservation, improving infrastructure, and cultural diversity. Community welcoming and support of local culture and ways of living enhance the experience of the visitor in this tourism sector. A good number of the Sustainable Development Goals (SDGs) concur with the research. SDGs 12 (Responsible Consumption and Production) and 15 (Life on Land) all give priority to conservation and nature's beauty. These two SDGs encourage sustainable operations. SDG 11, which is Sustainable Cities and Communities, stipulates that local culture integrated into tourism supports sustainable cities and communities’ development actions.